Actualize The Coastal Ecosystem Resilience : Determining The Location Of Artficial Reef - Andik Isdianto; Oktiyas Muzaky Luthfi (Journal of Innovation and Applied Technology, 2020)
Oceanographic parameters that affect coral reef growth are clarity, temperature, salinity and water currents taken at 20 stations using AAQ Rinko 1183 and FLOWATCH FL-03 current meter. The data processing using the IDW (Inverse Distance Weighted) interpolation method and the determination of the suitability area through scoring and weighting. The identification value consist of: (a) Clarity ranges from 2 - 6 meters, (b) Water turbidity ranges from 0.3 - 4.32 NTU, (c) Bottom substrate type is fine black sand, (d) Current velocity ranges from 0.1 m/s - 0.4 m/s, and (e) TSS ranges from 35.6 - 351 mg / L. The suitability of placing artificial reefs is classified at the appropriate level (S2), as a support for the survival of fishermen and local communities in Damas Beach, Trenggalek Regency.